P‐Type MoS2 and n‐Type ZnO Diode and Its Performance Enhancement by the Piezophototronic Effect. Issue 17 (3rd March 2016) - Xue, Fei; Chen, Libo; Chen, Jian; Liu, Jingbin; Wang, Longfei; Chen, Mengxiao; Pang, Yaokun; Yang, Xiaonian; Gao, Guoyun; Zhai, Junyi; Wang, Zhong Lin
Abstract : A plasma‐induced p‐type MoS2 flake and n‐type ZnO film diode, which exhibits an excellent rectification ratio, is demonstrated. Under 365 nm optical irradiation, this p–n diode shows a strong photoresponse with an external quantum efficiency of 52.7% and a response time of 66 ms. By increasing the pressure on the junction to 23 MPa, the photocurrent can be enhanced by a factor of four through the piezophototronic effect.